Efektivitas Penyelesaian Keberatan Retribusi Kebersihan di Dinas Pendapatan Daerah Kota Manado - Ismayanti, Fyfiannie; Rantung, Ventje V (JURNAL ILMU ADMINISTRASI (JIA), 2013)
Abstract: This research aims at examining the effectiveness of settling the objection of waste retribution which is based on the time accomplished, coordination within relevant technical institutions and the capability of human resources at Local Revenue Office of Manado City. This study used qualitative research and the data were collected through interviews, direct observing and documentation. The informants were obtained based on the consideration of the researcher, i.e. they are deemed able to provide objectives and accurate information in accordance with the research problem. The informants from the civil servants of the Local Revenue Office of Manado City were 3 persons and 5 persons from the compulsory of cleanliness retribution so the total number of all informants was 8 persons. The results of this study show that those involved in a compulsory retribution were generally satisfied with the service but they did not feel satisfied with the follow-up of results of the report’s objection. Thus it is suggested that in order to improve the performance of employees required upgrading the capacity in terms of employees’ active participation in education and functional training on local taxes and retribution, the working motivation of employees and compensation. Keywords: effectiveness of settling the objection, waste retribution